Description of the Manganese Collection at HIG - James E Andrews; Charles W Landmesser; M Morgenstein (PANGAEA, 1973)
The properties of ferromanganese concretions reflect in many ways the marine environment in which they were formed, and points to a variety of probable genetic mechanisms in different environments. There are also chemical and probably mineralogical variations which follow the various growth habits, and are a function of the environment. This report presents morphologic descriptions of the HIG manganese collection. Material described here was collected by the Hawaii Institute of Geophysics and Department of Oceanography during cruises of the R/V MAHI (1968-70), R/V KANA KEOKI (1971-72), and R/V TERITU (1971-72) and during the experimental test of a Continuous Line Bucket nodule retrieval experiment with the Japanese R/V Koyukoyu_Maru_II in 1972.